18F‐NaF PET/CT IMAGING IN FIBROUS DYSPLASIA OF BONE. (22nd May 2019) - Papadakis, Georgios Z; Manikis, Georgios C; Karantanas, Apostolos H; Florenzano, Pablo; Bagci, Ulas; Marias, Kostas; Collins, Michael T; Boyce, Alison M
ABSTRACT: Fibrous dysplasia (FD) is a mosaic skeletal disorder resulting in fractures, deformity, and functional impairment. Clinical evaluation has been limited by a lack of surrogate endpoints capable of quantitating disease activity. The purpose of this study was to investigate the utility of 18 F‐NaF PET/CT imaging in quantifying disease activity in patients with FD. Fifteen consecutively evaluated subjects underwent whole‐body 18 F‐NaF PET/CT scans, and FD burden was assessed by quantifying FD‐related 18 F‐NaF activity. 18 F‐NaF PET/CT parameters obtained included (i) SUVmax (standardized uptake value [SUV] of the FD lesion with the highest uptake); (ii) SUVmean (average SUV of all 18 F‐NaF–positive FD lesions); (iii) total volume of all 18 F‐NaF–positive FD lesions (TV); and (iv) total FD lesion activity determined as the product of TV multiplied by SUVmean (TA =  TV ×  SUVmean ) (TA). Skeletal outcomes, functional outcomes, and bone turnover markers were correlated with 18 F‐NaF PET/CT parameters. TV and TA of extracranial FD lesions correlated strongly with skeletal outcomes including fractures and surgeries ( p values ≤ 0.003). Subjects with impaired ambulation and scoliosis had significantly higher TV and TA values ( P < 0.05), obtained from extracranial and spinal lesions, respectively. Craniofacial surgeries correlated with TV and TA of skull FD lesions ( P < 0.001). Bone turnover markers, including alkaline phosphatase, N‐telopeptides, and osteocalcin, were strongly correlated with TV and TA ( P < 0.05) extracted from FD lesions in the entire skeleton. No associations were identified with SUVmax or SUVmean . Bone pain and age did not correlate with 18 F‐NaF PET/CT parameters. FD burden evaluated by 18 F‐NaF‐PET/CT facilitates accurate assessment of FD activity, and correlates quantitatively with clinically‐relevant skeletal outcomes. © 2019 American Society for Bone and Mineral Research.